Plant protection from virus: a review of different approaches - Anikina, Irina; Kamarova, Aidana; Issayeva, Kuralay; Issakhanova, Saltanat; Mustafayeva, Nazymgul; Insebayeva, Madina; Mukhamedzhanova, Akmaral; Khan, Shujaul Mulk; Ahmad, Zeeshan; Lho, Linda Heejung; Han, Heesup; Raposo, António (Frontiers in Plant Science, 2023)
This review analyzes methods for controlling plant viral infection. The high harmfulness of viral diseases and the peculiarities of viral pathogenesis impose special requirements regarding developing methods to prevent phytoviruses. The control of viral infection is complicated by the rapid evolution, variability of viruses, and the peculiarities of their pathogenesis. Viral infection in plants is a complex interdependent process. The creation of transgenic varieties has caused much hope in the fight against viral pathogens. The disadvantages of genetically engineered approaches include the fact that the resistance gained is often highly specific and short-lived, and there are bans in many countries on the use of transgenic varieties. Modern prevention methods, diagnosis, and recovery of planting material are at the forefront of the fight against viral infection. The main techniques used for the healing of virus-infected plants include the apical meristem method, which is combined with thermotherapy and chemotherapy. These methods represent a single biotechnological complex method of plant recovery from viruses in vitro culture. It widely uses this method for obtaining non-virus planting material for various crops. The disadvantages of the tissue culture-based method of health improvement include the possibility of self-clonal variations resulting from the long-term cultivation of plants under in vitro conditions. The possibilities of increasing plant resistance by stimulating their immune system have expanded, which results from the in-depth study of the molecular and genetic bases of plant resistance toward viruses and the investigation of the mechanisms of induction of protective reactions in the plant organism. The existing methods of phytovirus control are ambiguous and require additional research. Further study of the genetic, biochemical, and physiological features of viral pathogenesis and the development of a strategy to increase plant resistance to viruses will allow a new level of phytovirus infection control to be reached.